Magnetorheological Fluid Based Devices Reported in 2013–2018: Mini-Review and Comment on Structural Configurations - Phu, Do Xuan; Choi, Seung-Bok (Frontiers in Materials, 2019)
This paper presents a mini-review of magnetorheological (MRF) fluid-based devices (MRF devices in short) including the brake, clutch, damper, and the mount reported from 2013 to 2018. MRF devices are usually designed based on three operating modes of MRF: flow mode, shear mode and squeeze mode. Each mode has its own characteristics for the high performance of application systems. Therefore, numerous design configurations of MRF devices have been proposed by many researchers. In this article, among many different MRF devices such as MRF brake, clutch, damper and MRF mount proposed over the last 6 years are examined in the sense of their structural configuration and operating principles. Certain advantages and demerits of each MRF device are also discussed. In addition, some useful design guidelines of MRF devices, which are absolutely different from developed MRF devices so far, are provided to enhance design simplicity and control performance.